[BP.12.05] A GENETIC VARIANT IN THE DISTAL ENHANCER REGION OF THE HUMAN RENIN GENE AFFECTS RENIN EXPRESSION. (September 2017) - Makino, Y.; Konoshita, T.; Nakaya, T.; Ichikawa, M.; Yamamoto, K.; Wakahara, S.; Ishizuka, T.
Abstract : Objective: The high heritability of plasma renin activity was confirmed in recent investigations. A variation located near the strong enhancer of the human renin gene (REN), C-5312T, has been shown to have different transcription activity levels depending on its allele: the 5312T allele shows transcription levels that are 45% greater than those of the 5312C allele. The purpose of this study was to confirm the hypothesis that variations in the enhancer region of the REN gene are involved in regulating renal expression of renin. Design and method: Sixty-four subjects with biopsy-proven renal diseases were included in this study (male/female: 35/29, age 41.9 ± 20.9 years, SBP/DBP 123.1 ± 23.7/73.4 ± 14.8 mmHg, s-Cr 0.93 ± 0.63 mg/dl). A genetic variant of REN, C-5312T, was assayed by PCR-RFLP and the TaqMan method. Total RNAs from a small part of the renal cortex were reverse-transcribed and amplified for REN and GAPDH with a real-time PCR system. Results: Logarithmically transformed expression values of the relative ratio of REN to GAPDH (10[Combining Macron] 3 ) were as follows (mean ± SE): CC (26 cases), 0.016 ± 0.005; CT (33 cases), 0.047 ± 0.021 (p = 0.41 vs. CC); TT (5 cases), 0.198 ± 0.194 (p = 0.011 vs. CC, p < 0.031 vs. CT). Thus, significant differences in REN expression were observed among the genetic variants. Conclusions: The results suggest that variants in the enhancer region of the human renin gene have an effect on the expression levels of renin in renal tissue; this observation is in good accordance with the results of the transcriptional assay.